Pemanfaatan Quantum GIS Cloud Untuk Pemetaan Polygon Area Kandang Peternakan di Wilayah Kabupaten Probolinggo - Moch Nur Qomaruddin; Amalia - Herlina; Sulistiyanto - - (Universitas Islam Lamongan, 2020)
Department of Husbandry and Animal Health (Disnakkeswan) Probolinggo, is a government agency that has data on livestock, one of which is the location mapping data for the stables. This data is needed by Disnakkeswan and the general public to find information on the location of the livestock sheds in the Probolinggo district. Currently, the data on the location of the cage which is owned by the agency is still in the form of excel table data. This creates difficulties for the Animal Husbandry and Animal Health Service (Disnakkeswan) and the general public when looking for information on the location of the livestock pen. Among other things, the difficulty made them have to waste time finding the location of the farm stables. Given the roles and responsibilities of the Department of Animal Husbandry and Animal Health (Disnakkeswan) Probolinggo Regency above, an application is needed that will support or facilitate this task. The information presented in the Geographical Information System mapping the location of livestock stalls is the location of the co-ordinates for beef cattle, dairy and ducks. which can provide information about the location (stables) of the farm in the form of a map using a geographic information system with QGis Cloud.